2016
DOI: 10.17755/esosder.258819
|View full text |Cite
|
Sign up to set email alerts
|

Harmanlanmiş Öğrenme Yaklaşiminin Öğretmen Adaylarinin Akademi̇k Başarisina Ve Güdülenme Düzeyi̇ne Etki̇si̇

Abstract: Bu çalışmada, harmanlanmış öğrenme ortamının öğretmen adaylarının başarısına ve güdülenmelerine etkisinin belirlenmesi amaçlanmıştır. Çalışmada, yarı-deneysel desen kapsamına giren "ön test-son test eşleştirilmiş kontrol gruplu desen" kullanılmıştır. Çalışma, 2012 -2013 öğretim yılı bahar yarıyılında, Siirt Üniversitesi Eğitim Fakültesi Đlköğretim Anabilim Dalı Matematik Öğretmenliği ile Sosyal Bilgiler Öğretmenliğinde okuyan 158 öğrenci ile gerçekleştirilmiştir. Deneysel çalışmada kullanılan "Đnsan Đlişkileri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Moreover, a majority of the literature had been found from a select few countries such as the USA [68,84], Canada [30,85], New Zealand [86], Indonesia [37,87], Malaysia, Turkey [55,70,73,[88][89][90][91][92][93], Ghana [94], Uganda [23] that can avail the infrastructures and other equipment for applying BL in educational practice. However, many regions on different continents still cannot avail themselves of the required technologies and instructional resources to benefit their education [95].…”
Section: Fields Identified Of Included Literaturementioning
confidence: 99%
“…Moreover, a majority of the literature had been found from a select few countries such as the USA [68,84], Canada [30,85], New Zealand [86], Indonesia [37,87], Malaysia, Turkey [55,70,73,[88][89][90][91][92][93], Ghana [94], Uganda [23] that can avail the infrastructures and other equipment for applying BL in educational practice. However, many regions on different continents still cannot avail themselves of the required technologies and instructional resources to benefit their education [95].…”
Section: Fields Identified Of Included Literaturementioning
confidence: 99%
“…On the other hand, when the studies investigating the effect of student-centered teaching applications in Turkey on the motivation toward science learning were examined, it was observed that different results were found. When the literature was reviewed, it was determined that cooperative learning models integrated with educational games (Yıldız, Şimşek, & Ağdaş, 2017), science experiments (Akıllı, Keskin, & Ay, 2017), cooperative learning (Doğru & Ünlü, 2012), educational games (Yenice, Tunç, and Yavaşoğlu, 2019), concept cartoons (Ayhan, 2017), project-based learning (Işık & Gücüm, 2013), problem-based learning supported with concept cartoons (İnel 2012), life-based learning (Demir, 2019), problem-based learning (Tekin, 2020), STEM (Yıldırım & Selvi, 2017), blended learning (Pesen & Oral, 2016;Meriçelli & Uluyol 2016), science notebook (Bıyık, 2016) and information graphs (Boyacı, 2019) positively affected students' motivation toward science learning. On the other hand, there are also studies in the literature stating that learning strategies and methods such as problem-based learning (Tekin & Yıldırım, 2020), blended learning (Gürdoğan and Bağ, 2019), technologically supported learning (Develi, 2017), material and experiment activities (Aytekin, 2018), REACT Strategy (Karaş & Gül, 2019), concept cartoons (Şahin, 2019, scientific stories supported by concept cartoons (Yılmaz, 2013), slow-transition animation technique (Çamloğlu, 2014;Pak, 2020) and STEM (Büyükpastırmacı, 2019;Parlakay and Koç, 2020) were found to have no effect on the students' motivations toward science learning.…”
Section: Motivation and Student-centered Teaching Applications For Sc...mentioning
confidence: 99%
“…Harmanlanmış öğrenmenin salt yüz yüze veya salt çevrimiçi öğrenmeye göre farklı değişkenler üzerindeki etkisini inceleyen karşılaştırmalı çalışmalar alanyazında da yer almaktadır. Harmanlanmış öğrenmenin salt yüz yüze veya salt çevrimiçi öğrenmeye göre farklı değişkenler üzerinde çok daha etkili olduğu yapılan araştırmalarda ortaya konmuştur (Bonk vd., 2006;Pesen, 2014;Rovai ve Jordan, 2004). Daha önce de belirtildiği gibi çalışmalarda özellikle odaklanılan nokta harmanlanmış öğrenmenin öğrenci öğrenmeleri üzerindeki etkisine yöneliktir (Boyle vd., 2003;Dziuban vd., 2006;Garnham ve Kaleta, 2002;Lim ve Morris, 2009;López-Pérez vd., 2011;O'Toole ve Absalom, 2003;Twigg, 2003).…”
Section: Tartışma Ve öNerilerunclassified
“…Harmanlanmış öğrenme, yüz yüze öğrenme ve çevrimiçi öğrenmenin dezavantajlarının minimize edilmesi ve her ikisinin avantajlı taraflarının bir araya getirilmesinin düşünülmesi üzerine ortaya çıkan eklektik bir yaklaşımdır (Finn ve Bucceri, 2004;Graham, 2006;Harding vd., 2005;Pesen, 2014;Whitelock ve Jelfs, 2003;Williams vd., 2008). Alan yazında harmanlanmış öğrenmeye dair pek çok tanımlama ile karşılaşılmakta (Driscoll, 2002;Garrison ve Kanuka, 2004;Jonas ve Burns, 2010;Osguthorpe ve Graham, 2003;Williams vd., 2008;Yen ve Lee, 2011) ancak tam olarak sınırları belli bir tanımın henüz belirlenmediği, her çalışmanın kendine özgü çerçevesinin olduğu ve mevcut tanımların ortak özellikler taşıdığı yapılan araştırmalarda da belirtilmektedir (Aygün, 2011;Bliuc vd., 2007;Osgerby, 2013;Picciano vd., 2013;Poon 2012;Sharpe vd., 2006).…”
Section: Introductionunclassified
See 1 more Smart Citation